Comparative efficacy of haloperidol and placebo for treatment of delirium induced by biperiden and LPS in adult male rats based on their learning style and change in their short term spatial memory - Abdollah Farhadi Nasab; Malihe Roozbakhsh; Naghmeh Bahrami (Journal of Craniomaxillofacial Research, 2021)
Background and Objectives: Delirium refers to acute loss of consciousness and is characterized by confused thinking and impaired orientation. It is a life-threatening, but reversible syndrome manifested by cognitive impairment, abnormal psychomotor activity and sleep disturbances. Due to high prevalence in hospitalized patients and high rate of morbidity and mortality, delirium significantly decreases the prognosis of hospitalized patients. Materials and Methods: This experimental animal study evaluated 54 adult male Wistar rats over 2 months of age that weighed 200 to 230g. Of all, 24 rats received biperiden (40mg/kg) while the remaining 24 received 50μg/kg LPS. Induction of delirium was ensured using a Y-maze after 3 hours. The control group included 6 rats The efficacy of different doses of haloperidol for treatment of delirium was assessed 3 h after injection using the Y-maze. Data were compared using one-way ANOVA followed by Tukey’s post-hoc test via GraphPad Prism. Results: Haloperidol at 0.1, 0.2 and 0.5mg/kg dosage significantly increased the percentage of spontaneous alternation and improved the memory, consciousness and learning compared with biperiden and LPS groups (P<0.01). No significant difference was noted between the haloperidol groups regarding efficacy (P>0.05). Conclusion: Delirium is characterized by attention deficit, impaired orientation, changes in memory, consciousness, perception and mood, and psychotic symptoms. Detection of the complete spectrum of delirium signs and symptoms in an animal that cannot talk (rat) is obviously difficult. Using of Y-maze can facilitate this problem. Keywords: Delirium; Y-maze; Biperiden; Haloperidol; Spatial memory.